Accuracy of four rapid diagnostic tests (RDTs) for human leptospirosis diagnosis in Indonesia - Farida Handayani; Endah Tri Widanarti; Citra W. Kusuma; Ristiyanto Ristiyanto; Amin Soebandrio; Muhammad Hussein Gasem (Microbiology Spectrum)
ABSTRACT Leptospirosis is an endemic zoonotic disease with protean clinical manifestations caused by pathogenic spirochetes of the Leptospira genus. The microscopic agglutination test (MAT) is the gold standard for leptospirosis diagnosis and can only be conducted in a reference laboratory. Therefore, alternative tests, such as the IgM anti-Leptospira rapid diagnostic test (RDT), are preferred for general use. In this study, we aimed to compare the accuracy of four products of anti-Leptospira IgM detection RDTs, which are available in Indonesia, against the gold standard of Leptospira MAT. This study was a diagnostic validation test using bioarchived serum from 364 human serum samples tested by MAT from August to September 2020 in Demak, Central Java, Indonesia. The four products were (i) Fokus Leptospira, (ii) Answer Leptospira, (iii) SD Bioline Leptospira IgG/IgM, and (iv) Uji Leptospira IgM, sequentially renamed RDT-1 to RDT-4. Interobserver agreements were analyzed using the kappa value. The diagnostic performance of the four RDTs were compared against MAT results as the gold standard. We also evaluated the combination of two RDTs’ performance, which were RDT (1 + 2), RDT (1 + 3), RDT (1 + 4), RDT (2 + 4), and RDT (3 + 4). We found that the kappa coefficients of RDT-1, RDT-2, and RDT-4 were greater than 80%, while RDT-3 had a moderate kappa value of 69.1%. RDT-1, RDT-2, and RDT-4 had moderate to good sensitivities of 78.2%, 74.3%, and 83.6%, respectively, while RDT-3 had the lowest sensitivity at 30.9%. RDT-3 demonstrated the highest specificity. RDT-2 showed the highest predictive value at 75.9%, while RDT-4 showed the highest negative predictive value at 96.9%. In addition, the combination of two RTDs provided better diagnostic performances. The four RDTs performed varied in their ability to diagnose leptospirosis, but only RDT-4 showed a sensitivity of more than 80%. We recommend caution in diagnosing only one RDT result. Testing by other RDTs and confirmation by MAT are strongly recommended.IMPORTANCEThe performance of the anti-Leptospira IgM antibody rapid diagnostic tests (RDTs) has yet to be evaluated. In this study, we compare the accuracy of these four RDTs available in Indonesia against the gold standard of Leptospira microscopic agglutination test (MAT). Utilizing the best performance of RDT in the point of care with limited facilities will be effective since MAT is complicated, laborious, and time-consuming if done at public health centers. The MAT requires maintaining the culture of each live Leptospira strain circulating in the region and needs trained personnel.